Effectiveness of auditory and tactile crossmodal cues in a dual-task visual and auditory scenario. Issue 5 (4th May 2017) - Hopkins, Kevin; Kass, Steven J.; Blalock, Lisa Durrance; Brill, J. Christopher
Abstract: In this study, we examined how spatially informative auditory and tactile cues affected participants' performance on a visual search task while they simultaneously performed a secondary auditory task. Visual search task performance was assessed via reaction time and accuracy. Tactile and auditory cues provided the approximate location of the visual target within the search display. The inclusion of tactile and auditory cues improved performance in comparison to the no-cue baseline conditions. In comparison to the no-cue conditions, both tactile and auditory cues resulted in faster response times in the visual search only (single task) and visual–auditory (dual-task) conditions. However, the effectiveness of auditory and tactile cueing for visual task accuracy was shown to be dependent on task-type condition. Crossmodal cueing remains a viable strategy for improving task performance without increasing attentional load within a singular sensory modality. Practitioner Summary: Crossmodal cueing with dual-task performance has not been widely explored, yet has practical applications. We examined the effects of auditory and tactile crossmodal cues on visual search performance, with and without a secondary auditory task. Tactile cues aided visual search accuracy when also engaged in a secondary auditory task, whereas auditory cues did not.